La teoría y la práctica en la universidad medieval - Pedro Carañana, Joan (CIAN-Revista de Historia de las Universidades, 2012)
The article examines the mission of the medieval university with regard to the development of links between theory and practice. In the years prior to the formal recognition of the universities by the papacy and the empire, education centers strived to transmit knowledge focused on the bios theoretikos. This perspective was the dominant ideal of the universit ythroughout the Middle Ages. However,with the progressive institutionalization of universities, the mission to link teaching with professions also developed. The links between theory and practice are apparent in the disciplines related to the papacy (theology, canon law) and the empire (Roman law), as well as in the field of medicine.
Keywords: Medieval university; mission; theory and practice; profession; social mediation